The Role of ICL1 and H8 in Class B1 GPCRs; Implications for Receptor Activation - Winfield, Ian; Barkan, Kerry; Routledge, Sarah; Robertson, Nathan J.; Harris, Matthew; Jazayeri, Ali; Simms, John; Reynolds, Christopher A.; Poyner, David R.; Ladds, Graham (Frontiers in Endocrinology, 2022)
The first intracellular loop (ICL1) of G protein-coupled receptors (GPCRs) has received little attention, although there is evidence that, with the 8th helix (H8), it is involved in early conformational changes following receptor activation as well as contacting the G protein β subunit. In class B1 GPCRs, the distal part of ICL1 contains a conserved R12.48KLRCxR2.46b motif that extends into the base of the second transmembrane helix; this is weakly conserved as a [R/H]12.48KL[R/H] motif in class A GPCRs. In the current study, the role of ICL1 and H8 in signaling through cAMP, iCa2+ and pERK1/2 has been examined in two class B1 GPCRs, using mutagenesis and molecular dynamics. Mutations throughout ICL1 can either enhance or disrupt cAMP production by CGRP at the CGRP receptor. Alanine mutagenesis identified subtle differences with regard elevation of Ca2+, with the distal end of the loop being particularly sensitive. ERK1/2 activation displayed little sensitivity to ICL1 mutation. A broadly similar pattern was observed with the glucagon receptor, although there were differences in significance of individual residues. At the CRF1 receptor, an insertion in ICL1 switched signaling bias between Ca2+ and cAMP. Molecular dynamics suggested that changes in ICL1 altered the conformation of ICL2 and the H8/TM7 junction (ICL4). For H8, alanine mutagenesis showed the importance of E3908.49b for all three signal transduction pathways, for the CGRP receptor, but mutations of other residues largely just altered ERK1/2 activation. Thus, ICL1 may modulate GPCR bias via interactions with ICL2, ICL4 and the Gβ subunit.